Principles for Training Students in Circular Economy Skills: Pedagogical and Ecological Areas - Melnychenko, Anatolii; Pohrebniak, Anna; Kostiunik, Olena; Shchepina, Tetiana; Derevianko, Denys (Journal of the University of Zulia, 2024)
The purpose of the study is to substantiate the principles of the formation of students’ competencies in the circular economy in the pedagogical and ecological aspect, taking into account the achievement of the sustainable development goals. The methodological basis of the research is the systematic approach, which in pedagogy is aimed at revealing the value of pedagogical objects, identifying their various forms, components, types and relationships between them, which makes it possible to present the acquisition of competences among students for activities in the conditions of the circular economy as a whole presentation of actions using various forms, methods, means of teaching students in heigher education institutions. In the article, the epistemology of social challenges in the direction of achieving the sustainable development goals due to the implementation of the principles of the circular economy and the need in this context for the formation of relevant competencies of students of higher education institutions is substantiated. The characteristics that should correspond to the competence of the circular economy according to the characteristics of the integrated quality of the individual have been determined. The components that form the competences of the circular economy have been identified, which include: axiological, cognitive, practical-technological, and institutional.